Korean phrasebook & dictionary - Gray, Shona (Lonely Planet, 2020)
Lonely Planet Korean Phrasebook & Dictionary is your handy passport to culturally enriching travels with the most relevant and useful Korean phrases and vocabulary for all your travel needs. Understand Korean script and navigate menus with ease; all with your trusted travel companion. With language tools in your back pocket, you can truly get to the heart of wherever you go, so begin your journey now!